Guidance on validation of lethal control measures for foodborne pathogens in foods. Issue 3 (7th May 2021) - Ceylan, Erdogan; Amezquita, Alejandro; Anderson, Nathan; Betts, Roy; Blayo, Laurence; Garces‐Vega, Francisco; Gkogka, Elissavet; Harris, Linda J.; McClure, Peter; Winkler, Anett; den Besten, Heidy M. W.
Abstract: Food manufacturers are required to obtain scientific and technical evidence that a control measure or combination of control measures is capable of reducing a significant hazard to an acceptable level that does not pose a public health risk under normal conditions of distribution and storage. A validation study provides evidence that a control measure is capable of controlling the identified hazard under a worst‐case scenario for process and product parameters tested. It also defines the critical parameters that must be controlled, monitored, and verified during processing. This review document is intended as guidance for the food industry to support appropriate validation studies, and aims to limit methodological discrepancies in validation studies that can occur among food safety professionals, consultants, and third‐party laboratories. The document describes product and process factors that are essential when designing a validation study, and gives selection criteria for identifying an appropriate target pathogen or surrogate organism for a food product and process validation. Guidance is provided for approaches to evaluate available microbiological data for the target pathogen or surrogate organism in the product type of interest that can serve as part of the weight of evidence to support a validation study. The document intends to help food manufacturers, processors, and food safety professionals to better understand, plan, and perform validation studies by offering an overview of the choices and key technical elements of a validation plan, the necessary preparations including assembling the validation team and establishing prerequisite programs, and the elements of a validation report.